Stability of cannabinoids in hair samples exposed to sunlight - Skopp, Gisela; Pötsch-Schneider, Lucia Edeltraud; Mauden, Jörg Martin (Clinical chemistry, 2000)
The cannabinoid content in the hair samples was determined by gas chromatography-mass spectrometry. Each strand was pulverized in a ball mill, and ∼50 mg of the hair powder was weighed; 25 ng of THC-d3 (Radian International) was added as internal standard, and the sample was further processed according to Cirimele et al. (12). A 1-μL aliquot of the extract was injected into a gas chromatography-mass spectrometry system [HP 6890 gas chromatograph and HP 6890 mass spectrometer, both from Hewlett Packard; column, CP-Sil 5, 12.5 m × 0.53 mm (i.d.), from Chrompack]. Detection was by ionization in the electron impact mode (70 eV), with the scan mode set at single-ion monitoring (THC, m/z 299, 314, 271; THC-d3, m/z 302, 317, 274; CBN, m/z 295, 310, 238; CBD, m/z 231, 246, 314). Measurements were taken twice from each strand. The THC concentrations determined from a particular sample differed by at least 15% and are given as mean values (n = 4; Table 1 ). Deuterated standards for CBN and CDB are not yet commercially available; hence, these compounds were not quantified, and triplicate measurements of six drug-free hair samples were used to estimate their particular detection limits (mean + 3 SD). The limit of detection was 0.05 ng/mg of hair for all analytes.